From Hashtag to Habit: A Social Network Analysis of Ethical Consumption and Consumer Brand Switching on Platform X - Azhar, Ratih Mukti; Arumsari, Devinta Nur (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the role of ethical discourse on social media in shaping consumer brand switching behavior as a response to social or political movements or challenges on Platform X. utilizing social network analysis (SNA) in the presence of Gephi, conversation data containing specific keywords were analyzed to map social network structures, identify communities, and assess the influence of central actors in the dissemination of values and collective calls to action. The outcomes reveal the formation of strong communities in the presence of relatively high modularity, selective interactions under the framework of community clusters, and the dominant role of influencer accounts in accelerating the diffusion of ethical discourse and calls for alternative consumption actions. The massive ethical advocacy process on social media not only shapes public opinion but also extends into the realm of consumer preference changes, where brand switching occurs as the implementation of solidarity values and ethical consumption. This study underscores the importance of social networks and consumer ethics in driving the transformation of consumption patterns in digital society and provides strategic implications for brand management in the era of worldwide challenges and collective ethics based on online communities.